Different Electrophysiological Responses to Pain-Related Visual Stimuli Between Fibromyalgia and Chronic low Back Pain Women: A Pilot Case-Control Study. (December 2021) - Lai, Carlo; Ciacchella, Chiara; Pellicano, Gaia Romana; Altavilla, Daniela; Sambucini, Daniela; Paolucci, Teresa; Sorgi, Maria Laura; Di Franco, Manuela; Saggini, Raoul; Aceto, Paola
Background: Fibromyalgia is a chronic pain syndrome which occurs in the absence of an organic damage, whom causes is still unclear. Aims of this pilot study were to investigate the neural correlates of fibromyalgia in response to pain-related visual stimuli and explore the psychological differences among fibromyalgia, chronic low back pain (CLBP) and healthy conditions. Methods: After a clinical assessment, electrophysiological responses to pain-related visual stimuli were recorded using a 256-Hydrocel Geodesic-Sensor-Net. Event-related potentials (ERPs), standardised low-resolution electromagnetic tomography (sLORETA), and psychological (Symptom Checklist-90-Revised) data were analysed for a total sample of 23 women (5 healthy volunteers, 12 fibromyalgia patients, 6 CLBP patients). Results: The main finding was that fibromyalgia women reported a different brain response to pain-related visual stimuli on the frontal montage compared to women with CLBP ( p  = .028). Moreover, fibromyalgia women showed an increased activity mainly on the hippocampus ( p  = .003) and the posterior cingulate cortex ( p  ≤ .001) in response to algic stimuli compared to not algic ones. Lastly, these women presented higher scores on the somatization ( p  = .002), obsession-compulsion ( p  = .045), depression ( p  = .043) and positive symptom distress ( p  = .023) dimensions compared to the healthy women. Conclusions: These preliminary results suggest that although the painful symptoms are similar, the central elaboration of pain could be different between women with fibromyalgia and those with CLBP. Moreover, these findings provide preliminary evidences about the great alert and the central sensitivity to pain-related information regarding fibromyalgia patients.